Biofilm inhibition mechanism of BiVO4 inserted zinc matrix in marine isolated bacteria. (10th June 2021) - Zhai, Xiaofan; Ju, Peng; Guan, Fang; Duan, Jizhou; Wang, Nan; Zhang, Yimeng; Li, Ke; Hou, Baorong
Graphical abstract: Abstract: Biofilm plays an important role on microbial corrosion and biofouling in marine environments. Inhibiting biofilm formation on construction surfaces is of great importance. Photocatalytic material with visible-light response, especially BiVO4, is regarded as a promising material for biofilm inhibition due to its green biocidal effect and high antibacterial efficiency. Approaches which can immobilize the photocatalytic particles onto metal surfaces with high mechanical strength are requisite. In this study, zinc matrixes were served as carriers for BiVO4 particles. The BiVO4 -inserted zinc matrixes were successfully obtained by ultrasound assisted electrodeposition. The insertion content of BiVO4 showed positive correlation with ultrasound power. Highly enhanced biofilm inhibition properties were obtained by BiVO4 inserted zinc matrixes with an over 95 % decreased bacterial coverage. It was proved that O2 − (chief) and OH (subordinate) radicals were responsible for the high biocidal performance. Possible antibacterial mechanism was proposed, indicating that the photoinduced holes would both attack zinc crystals to generate active electrons to form O2 − radicals, and react with H2 O to generate OH, finally. Furthermore, corrosion resistance of the matrixes was proved to be stable due to the insertion of BiVO4 . This study provides a potential application for photocatalyst in marine antifouling and anti-biocorrosion aspects.